CHARACTERIZATION OF WASTES FROM SEPTAGE COLLECTION AND TRANSPORT TRUCKS IN THE FEDERAL DISTRICT, BRAZIL - Lisboa, Adriane Dias da Silva; Ginoris, Yovanka Pérez; Souza, Marco Antonio Almeida de (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2021)
Abstract In the Federal District of Brazil, the cleaning waste from on-site sanitation facilities is transported by septage trucks to sewage treatment plants (STPs) to be treated in conjunction with sewage. This research aimed to characterize the waste from septage trucks that were discharged in the two STPs in Brasilia, Federal District of Brazil. The methodology included the characterization (sampling and laboratory tests) of waste samples collected from septage trucks that discharged waste at the two STPs in Brasília, and the collection of information on the origin of this waste and the frequency of cleaning the on-site sanitation units. Great variability was found in the frequency of cleaning cesspools and septic tanks. The cleaning of the on-site sanitation facilities took place daily in some places and monthly in the remaining sites, and eventually, facilities with annual cleaning were reported. The characteristic that had the lowest variation coefficient was the pH. The presence of large concentrations of oils and greases in the residues of the septage trucks is a major inconvenience. The results obtained contribute to the knowledge of the characteristics of waste from septage trucks, its management and proper treatment. Keywords: septage; grease trap waste; septage collection and transport truck; oil and grease. CARACTERIZAÇÃO DOS RESÍDUOS DOS CAMINHÕES LIMPA-FOSSAS NO DISTRITO FEDERAL, BRASIL Resumo No Distrito Federal, os resíduos da limpeza das instalações de tratamento descentralizado de esgoto são transportados por caminhões limpa-fossas para as estações de tratamento de esgoto (ETEs) para serem tratados em conjunto com o esgoto. Esta pesquisa teve como objetivo caracterizar os resíduos de caminhões limpa-fossas que descarregaram nas duas ETEs de Brasília, Distrito Federal, Brasil. A metodologia incluiu a caracterização (amostragem e exames laboratoriais) de amostras de resíduos coletadas dos caminhões limpa-fossas que descarregaram lodo de fossa nas duas ETEs de Brasília, e a coleta de informações sobre a origem desses resíduos e a frequência de limpeza das unidades de tratamento descentralizado de esgoto. Encontrou-se grande variabilidade nas frequências de limpeza de fossas e tanques sépticos. A limpeza das instalações de tratamento descentralizado de esgotos ocorria diariamente em alguns locais e mensalmente nos demais e, eventualmente, foram registradas instalações com limpeza anual. O pH foi a característica que apresentou o menor coeficiente de variação. A presença de grandes concentrações de óleos e graxas nos resíduos dos caminhões limpa-fossas é um grande inconveniente. Os resultados obtidos contribuem para o conhecimento das características dos resíduos de caminhões limpa-fossas, sua gestão e tratamento adequado. Palavras-chave: lodo de fossas e tanques sépticos; resíduos de caixas de gordura; caminhões limpa-fossas; óleos e graxas.